Controllable cyanation of carbon-hydrogen bonds by zeolite crystals over manganese oxide catalyst - Liang Wang (Nature Portfolio, 2017)
Sustainable strategies for nitrile synthesis are needed. Here, the authors report an environmentally benign, selective heterogeneous catalyst for the synthesis of nitriles by the oxidative cyanation of carbon and hydrogen (C-H) bonds, which comprises nanoscale manganese oxide catalysts fixed inside a zeolite crystal.